An ultrasonic signal reconstruction algorithm of multilayer composites in non-destructive testing. (15th January 2022) - Li, Yiming; Yao, Kai; Li, Xinglong
Abstract: With the wide application of composite materials in various fields, efficient and reliable non-destructive testing technology has been developed in a general manner. Due to the technical constraints and environmental changes in the composite material preparation process, there are many defects, such as debonding and unequal thickness. Ultrasonic testing, being a non-destructive testing method, has been widely used in many areas because of its convenience and effectiveness. In this paper, a new self-interference cancellation algorithm based on the matching pursuit algorithm is proposed, which can eliminate the waveform generated by multiple reflections in the echoed signal. A two-dimensional finite element model with multiple defects of composite materials is established to simulate the actual process of damage detection. The calculated damage location is compared with the model's actual parameters, which shows that the algorithm can be applied to the defect location of multilayer composites. A multilayer structure ultrasonic experiment is established and the good performance of the algorithm has been verified.